2019
DOI: 10.1161/hypertensionaha.118.12205
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic Factor Estimation as a Warning Sign of Preeclampsia-Related Peripartum Morbidity Among Hospitalized Patients

Abstract: Preeclampsia-related morbidity and mortality is rising predominantly because of delayed identification of patients at risk for preeclampsia with severe features and associated complications. This study explored the association between angiogenic markers (sFlt1 [soluble fms-like tyrosine kinase-1]) and PlGF [placental growth factor]) and preeclampsia-related peripartum complications. Normotensive women or those with hypertensive disorders of pregnancy were enrolled. Blood samples were collected within 96 hours … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 15 publications
0
11
0
2
Order By: Relevance
“…129 The rate of elevation in the antepartum soluble fmslike tyrosine kinase 1/placental growth factor ratio is an independent predictor of hypertension that persists postpartum. 130 Furthermore, preeclampsia-associated endothelial dysfunction and altered cerebrovascular autoregulation have been shown to persist postpartum 131 and may amplify postpartum hypertension risk. Intravenous fluids, mobilization of extravascular fluid, and use of nonsteroidal anti-inflammatory drugs for postpartum analgesia may contribute to its occurrence.…”
Section: Postpartum Hypertension and Postpartum Preeclampsiamentioning
confidence: 99%
“…129 The rate of elevation in the antepartum soluble fmslike tyrosine kinase 1/placental growth factor ratio is an independent predictor of hypertension that persists postpartum. 130 Furthermore, preeclampsia-associated endothelial dysfunction and altered cerebrovascular autoregulation have been shown to persist postpartum 131 and may amplify postpartum hypertension risk. Intravenous fluids, mobilization of extravascular fluid, and use of nonsteroidal anti-inflammatory drugs for postpartum analgesia may contribute to its occurrence.…”
Section: Postpartum Hypertension and Postpartum Preeclampsiamentioning
confidence: 99%
“…Circulating angiogenic factors measured during the third trimester have also been implicated in immediate postpartum hypertension and peripartum morbidity. 207 , 208 Studies using advanced echocardiography have also shown that global longitudinal strain (GLS) with speckle tracking echocardiography is a sensitive measure of the onset of subclinical cardiac dysfunction in PE, and these changes correlate with alterations in circulating sFLT1 and sENG. 209 , 210 Because GLS differentiates active from passive contraction and is less sensitive to loading conditions than ejection fraction, it reliably detects the early onset of subclinical systolic heart failure in patients with PE.…”
Section: Angiogenic Factors and Cardiovascular Diseasementioning
confidence: 99%
“…Підвищення рівня sFlt-1 і зниження PlGF більш різко змінюються при передчасній ПЕ та/або при ПЕ, ускладненій затримкою росту плода [23,24]. У кількох звітах припускають, що ангіогенні фактори, виміряні наприкінці ІІ і ІІІ триместрів, можуть допомогти у діагностиці ПЕ та прогнозуванні несприятливих наслідків із високою чутливістю та специфічністю [25][26][27][28]. Важливо відзначити, що підвищені рівні sFlt-1:PlGF корелювали з ймовірними передчасними пологами, що підтверджено кількома групами [29,30].…”
Section: Methodsunclassified